Colonizing the fantastic: Reading Stephenie Meyer's Breaking Dawn as all-in-one text - Baysar Tanıyan (Literacy Trek, 2020)
As the life on the planet gets more and more complicated due to the rapid changes in the socio-cultural paradigms, the task of boundary drawing, categorization or classification appears as a hazardous task. Likewise, while Stephenie Meyer's The Twilight series is generally classified as fantasy, all four novels in the series resist such a simplified classification when tested with the key ideas of Todorov's insistence on hesitation, Rosemary Jackson's perception of the fantastic as a deconstructive mode or Rabkin's idea of fantastic effect. The article will argue that the last novel of the series, Breaking Dawn, exploits various genres while trying to remain in the realm of fantasy. These genres may be listed as romance, erotic romance, uncanny (or the fantastic), epic and, finally, the fairy tale. The novel surpasses the drawn boundaries of different genres without committing itself to any of them and, therefore, the text becomes what might be called an 'all-in-one text'. It is not just a singular fantastic text but a pluralistic all-in-one text enabling the reader to experience different reading pleasures in one text, which might provide valuable ideas to better understand the general spirit of the postmodern age and the consumerist habits of postmodern readers.